PERBANDINGAN EFISIENSI PADA PREPARATION VOUCHER SEBELUM DAN SESUDAH PENERAPAN TRANSFORMASI DIGITAL DI TANJUNG KODOK BEACH RESORT - Damayanti, Dyah Ayu; Astuti, Anindita Budi; Pirastyo, Swastono Putro (Jurnal Perhotelan dan Pariwisata, 2023)
Abstract Digital transformation serves as a solution for improving operational efficiency in the hospitality industry. One process that requires optimization is voucher preparation, which is still conducted manually in many establishments. This study aims to compare work efficiency between manual and QR Code–based Digital systems in the preparation voucher process. A qualitative method was used, with data collected through observation, interviews, and workflow simulations. The findings indicate that QR Code implementation has the potential to streamline workflow, reduce staff workload, minimize recording errors, and support practical service digitalization. The study recommends adopting the QR Code–based Digital system as a more efficient and environmentally friendly alternative in hotel operations. Keywords: QR Code; Digital transformation; work efficiency; manual voucher; hotel service.